A pilot study on the feasibility of atis leaves as a potential mosquito repellent laundry aid - Latosa, Gloria Teresa Q.; Caragay, Kristyn T. (Quezon City UP College of Home Economics, 2012)
ABSTRACT Mosquitoes are the most significant agents in the transmission of several human diseases among insects. Mosquito vectors are commonly present in tropical regions such as Philippines where the dengue incidents are alarmingly on the rise. This study was developed with the deterrence of human-mosquito interaction in mind and the goal of providing a more environment friendly alternative to chemical mosquito repellents. This experimental research explored the possibility of the atis leaves as a potential mosquito repellent laundry aid. The research aims to identify the degree of effectiveness of the atisinfused fabric conditioner via the mosquito bioassay, assess the side effects of the application of atis infused fabric conditioner to poly-blended cotton and polyester mosquito net and evaluate the commercial viability of the product. At 10% concentration, only one out of three atis treated black poly-cotton samples garnered a passing mark in the mosquito bioassay. The atis-fabric conditioner solution caused significant staining on light colored samples, had a less visible effect on the dark colored samples, and produced green lumps in between the mosquito net fibers. The atis-fabric conditioner solution had the same duration of protection with the citronella oil, was convenient to use, and had low skin toxicity. The researcher recommends formulating the solution at a higher concentration to function as a more substantial supplement to the commercially available mosquito repellents and to strengthen the protection against mosquitoes and the diseases they transmit.
Thesis (BSCT)--University of the Philippines Diliman
Keywords: Insect baits and repellents -- Philippines; Atis leaves